Neutral Sphingomyelinase is an Affective Valence-Dependent Regulator of Learning and Memory. (12th October 2020) - Kalinichenko, Liubov S; Abdel-Hafiz, Laila; Wang, An-Li; Mühle, Christiane; Rösel, Nadine; Schumacher, Fabian; Kleuser, Burkhard; Smaga, Irena; Frankowska, Malgorzata; Filip, Malgorzata; Schaller, Gerd; Richter-Schmidinger, Tanja; et al.
Abstract: Sphingolipids and enzymes of the sphingolipid rheostat determine synaptic appearance and signaling in the brain, but sphingolipid contribution to normal behavioral plasticity is little understood. Here we asked how the sphingolipid rheostat contributes to learning and memory of various dimensions. We investigated the role of these lipids in the mechanisms of two different types of memory, such as appetitively and aversively motivated memory, which are considered to be mediated by different neural mechanisms. We found an association between superior performance in short- and long-term appetitively motivated learning and regionally enhanced neutral sphingomyelinase (NSM) activity. An opposite interaction was observed in an aversively motivated task. A valence-dissociating role of NSM in learning was confirmed in mice with genetically reduced NSM activity. This role may be mediated by the NSM control of N -methyl-d -aspartate receptor subunit expression. In a translational approach, we confirmed a positive association of serum NSM activity with long-term appetitively motivated memory in nonhuman primates and in healthy humans. Altogether, these data suggest a new sphingolipid mechanism of de-novo learning and memory, which is based on NSM activity.